Malaria Prevalence and Associated Factors in Children Under Five Years in Dokolo District, Northern Uganda: A Community-Based Cross-Sectional Study - Adooli, Emmanuel; Driciru, Hellen; Nakiyingi, Maria; Onencan, Patrick M; Teeka, Mariam; Kalyetsi, Rogers; Muwanguzi, Enoch; Nsubuga, Edirisa J; Migisha, Richard; Byaruhanga, Aggrey (Annals of Epidemiology and Public Health, 2023)
Introduction: Malaria remains a major public health problem affecting children <5 years because of the weak im¬mune system. Uganda set targets to control and eliminate malaria with interventions of most at-risk groups; however, infection rates remain high in Northern Uganda, especially Lango region. This study determined the prevalence and risk factors of malaria and identified among children <5 years in Agwata Sub-county, Dokolo District, Northern Uganda. Methods: We conducted a cross-sectional study among children aged six months to <5 years in Agwata Subcounty in Dokolo District from 25 April to 10 May, 2021. A three-stage sampling method was used to select participants. Blood samples were examined by smear microscopy for malaria parasites, and ABO blood grouping system was used to es¬tablish blood groups of the study participants. Data on de¬mographics and malaria exposure were captured using an interviewer-administered semi-structured questionnaire. Multivariable logistic regression was used to identify factors associated with malaria. Results: We enrolled 405 children with a mean age of 2.5 (±SD, 1.4-3.6) years; 53% were male. Of these, 118 tested positive for malaria with a prevalence of 29% (95%CI: 24.7-33.8%). Having blood group, A (aOR= 1.7, 95% CI:1.1-2.7), households with >3 children (aOR= 2.6, 95% CI: 1.5-4.5), rural residence (aOR=5.7,95% CI: 3.5-8.6), absence of long lasting insecticidal mosquito nets (LLINs) over the children’ beds (aOR=5.1, 95% CI: 2.8-7.4), presence of holes in the LLINs (aOR=2.2, 95% CI: 1.5-4.1) and children staying in traditional households (aOR=4.2, 95% CI: 2.4-8.6) were sig¬nificantly associated with malaria. Conclusion: Approximately one-third of the children <5 years in this survey had malaria, highlighting a high malar¬ia burden in Dokolo District. Children with blood group A, those staying in households of >3 children, those from poor or rural households, and those from households with poor use of LLINs were more likely to be diagnosed with malaria compared to their counterparts. There is a need for routine screening and chemoprophylaxis in children for malaria, given the high malaria burden. The community should be availed with LLINs and sensitized on their proper use.
Keywords: Malaria; Long Lasting Treated Mosquito Nets; Plasmodium falciparum